GIS based decision support system and its application in agroforestry - Singh, J.P.; Roy, M.M. (Indian Journal of Agroforestry, 2020)
Appropriate decision support systems based on available information and modern tools and technologies may serve as a valuable aid in dissemination of information in the field of agro forestry for the benefit of the end user. The computer based models may be extremely useful in efficient handling of many of the social, economic and ecological variables in a simplified manner. GIS is likely to play an important role in the integration of various types of spatial and non spatial data set on a single platform and provide desired information in the form of maps and feature linked dataset. Also, such information may be essential for answering many of the quarries related to agro forestry interventions in an area.